A critical overview of the current myofascial pain literature – November 2018. Issue 1 (January 2019) - Dommerholt, Jan; Hooks, Todd; Chou, Li-Wei; Finnegan, Michelle
Abstract: This is the first issue of this review column since the passing of Dr. Leon Chaitow. We would like to take a brief moment to acknowledge how much his mentorship, friendship, and confidence have meant to us. Leon was a force in osteopathic and naturopathic medicine and his influence reaches to all corners of the musculoskeletal realm crossing over many disciplines through his lectures, workshops, and of course, his many books, editorials, and articles. In the foreword to one of his books, Jan Dommerholt wrote that "Leon Chaitow […] continued the work of Travell and Simons, but also of many others, whose contributions he has skillfully woven into an intricate tapestry of clinical pearls, practical tips, and solid evidence-informed research." Dr. Chaitow was a synthesizer, who always considered what different clinicians and researchers could possibly contribute to a better understanding of pain and dysfunction and provide real solutions to real problems. Even when he would not necessarily agree with all suggested remedies, he maintained an open mind and was able to take a step back and consider the bigger picture. For example, Leon was not a big fan of dry needling, yet, he valued the importance of this approach and encouraged the inclusion of dry needling papers in this review article and in his journal. The Journal of Bodywork and Movement Therapies became his baby and, considering the growth of the journal, there is no question that Leon's intense focus and efforts are appreciated by many around the globe. We wish to extend our condolences to Leon's wife Alkmini and daughter Sasha. He will surely be missed, but we can find peace in knowing that his legacy will stay with us forever. In this issue, we have included several basic myofascial pain research articles. As usual, dry needling (DN) studies and case reports are the most commonly referenced papers, but we also included neuroscience and electromyography studies, sleep studies, interrater reliability studies, and case reports of adverse events.